MicroRNAs in idiopathic pulmonary fibrosis: involvement in pathogenesis and potential use in diagnosis and therapeutics - Huimin Li; Xiaoguang Zhao; Hongli Shan; Haihai Liang (Elsevier, 2016)
MicroRNAs (miRNAs) are a class of phylogenetically conserved, non-coding short RNAs, 19-22 nt in length which suppress protein expression through base-pairing with the 3'-untranslated region of target mRNAs. miRNAs have been found to participate in cell proliferation, differentiation and apoptosis. Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and high lethality fibrotic lung disease for which currently there is no effective treatment. Some miRNAs have been reported to be involved in the pathogenesis of pulmonary fibrosis. In this review, we discuss the role of miRNAs in the pathogenesis, diagnosis and treatment of IPF.